2019
DOI: 10.1088/1757-899x/579/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Performance Simulation for Gas Flow through a Porous Media in Packed bed Columns using CFD

Abstract: Two dimensions of Computational Fluid Dynamics simulation for gas flow in the column with filling material as bed at low particle Reynolds numbers and high particle Reynolds numbers have been presented. The simulation test has been done with the column length 0.9 m. Porous media model was used to simulate the gas flow inside porous granular media. Model of standard k-e for the flow turbulent range was used; the difference on the mesh size used to study effect it on the performance of gas flow through porous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Compared with traditional CFD-PBM simulations, the coupled model can greatly improve the simulation of DSD, Sauter mean diameter, median diameter, and span for highly dispersed phase quantities (DPA). Salim Bded 11 investigated the effect of viscosity changes on natural convection in a confined space and predicted the flow field and heat transfer in a bilayer porous medium using the Darcy model in a commercial CFD package, but did not simulate or analyze the concentration field. Bai et al 12 simulated the fixed bed adiabatic adsorption/desorption process and calculated the heat and mass transfer rates using the LDF model.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional CFD-PBM simulations, the coupled model can greatly improve the simulation of DSD, Sauter mean diameter, median diameter, and span for highly dispersed phase quantities (DPA). Salim Bded 11 investigated the effect of viscosity changes on natural convection in a confined space and predicted the flow field and heat transfer in a bilayer porous medium using the Darcy model in a commercial CFD package, but did not simulate or analyze the concentration field. Bai et al 12 simulated the fixed bed adiabatic adsorption/desorption process and calculated the heat and mass transfer rates using the LDF model.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadpour et al [30] demonstrated the feasibility of CFD method in packed beds, and used CFD method to simulate the influence from different turbulence models. Bded et al [31] presented a study of CFD simulation for gas flow in the column with filling material as the bed at low particle Reynolds numbers and high particle Reynolds numbers. Teitel et al [32] assumed the woven screen geometry as a porous medium and determined the pressure drops through mono-filament woven screens utilizing CFD simulations.…”
Section: Introductionmentioning
confidence: 99%